2022
DOI: 10.1186/s12885-022-09405-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficiency of lenvatinib plus PD-1 blockades in advanced hepatocellular carcinoma: an exploration for expanded indications

Abstract: Background This study aimed to evaluate the efficiency and prognostic factors of lenvatinib plus programmed death 1 (PD-1) blockades in patients with advanced hepatocellular carcinoma (HCC), especially for those with tumor occupation ≥50% volume of liver (TO ≥50%) or invasion in Vp4, who were excluded from the trial KEYNOTE-524. Methods We reviewed the clinical data of patients with unresectable HCC who received lenvatinib plus PD-1 blockades. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…For the tumor response, the RESCUE trial ( 6 ) disclosed an ORR of 34.3% and a DCR of 77.1% following combined apatinib and camrelizumab therapy. The TACE + AC group had a greater ORR compared to those reported by the IMbrave150 trial ( 7 ) (atezolizumab plus bevacizumab: ORR = 33.2%), the phase 1b KEYNOTE-524 trial ( 22 ) (lenvatinib plus pembrolizumab: ORR = 46.0%), and the ORIENT-32 trial (sintilimab plus bevacizumab: ORR = 24%); this was likely because the addition of TACE is thought to be related to immune activation and can induce low expression of Tregs via modulating pro-inflammatory pathways. In our study, the CR, ORR, and DCR rates of the TACE + AC group were numerically greater than those of the TACE + A group (11.8% vs. 5.9%, 55.9% vs. 51.5%, and 79.4% vs. 72.1%, respectively), although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 79%
“…For the tumor response, the RESCUE trial ( 6 ) disclosed an ORR of 34.3% and a DCR of 77.1% following combined apatinib and camrelizumab therapy. The TACE + AC group had a greater ORR compared to those reported by the IMbrave150 trial ( 7 ) (atezolizumab plus bevacizumab: ORR = 33.2%), the phase 1b KEYNOTE-524 trial ( 22 ) (lenvatinib plus pembrolizumab: ORR = 46.0%), and the ORIENT-32 trial (sintilimab plus bevacizumab: ORR = 24%); this was likely because the addition of TACE is thought to be related to immune activation and can induce low expression of Tregs via modulating pro-inflammatory pathways. In our study, the CR, ORR, and DCR rates of the TACE + AC group were numerically greater than those of the TACE + A group (11.8% vs. 5.9%, 55.9% vs. 51.5%, and 79.4% vs. 72.1%, respectively), although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 79%
“…Study characteristics are shown in eTable 1 in Supplement 1. In summary, 19 of the 22 studies were retrospective, 3 were prospective, 6 evaluated nivolumab, 4 evaluated nivolumab and pembrolizumab, 1 evaluated camrelizumab, 1 evaluated pembrolizumab, 5 evaluated atezolizumab, and the remaining 5 did not describe detailed agents . The median patient age ranged from 53 to 73 years among included studies.…”
Section: Resultsmentioning
confidence: 99%
“… 25 Interestingly, we noticed that a recently reported retrospective study initiated by Sun et al explored the real-world effectiveness of lenvatinib plus PD-1 inhibitors in advanced HCC. 26 A total of 84 patients with HCC receiving lenvatinib plus PD-1 blockades were recruited for retrospective analysis, including 31 patients with tumor occupation ≥50% and 30 patients with Vp4 invasion, which resulted in an ORR of 20.2%, a DCR of 40.5%, a median PFS of 6.6 months and a median OS of 11.4 months. Obviously, the clinical outcomes in this study seemed to be worse compared with those in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Therefore, patients enrolled in this study were representative of the patients with HCC in China and the finding that patients with HBV infection might benefit from lenvatinib plus PD-1 blockades were in concert with the study reported previously. 26 Collectively, clinical outcomes of lenvatinib plus PD-1 blockades among patients with unresectable advanced HCC should be elucidated in prospective clinical trials in the future.…”
Section: Discussionmentioning
confidence: 99%